Effects of wood species, connection system, and wall-support interface type on cyclic behaviors of cross-laminated timber (CLT) walls under lateral loads. (19th April 2021) - Tran, Dang Khai; Jeong, Gi Young
Highlights: Nonlinear behaviors of different configurations of CLT walls. Elasto-plastic curves of CLT walls with different support conditions. Lateral resistance properties of CLT walls made from different density. Uplift-sliding interaction of CLT walls from different connection systems. Hysteric behaviors of different configurations of CLT walls using SAWS models. Abstract: The goal of this study is to investigate the effects of wood species, connection systems, and wall-support interface types on the cyclic behaviors of cross-laminated timber (CLT) walls under lateral loads. We developed a CLT wall SAWS model for lateral behaviors associated with different configurations. CLT walls with a higher density and a rigid support showed greater strength and lower deformation as compared to CLT walls having a lower density with a flexible support. CLT walls using hold-downs to carry the up-lift forces showed greater strength properties (16.9 to 96.7%) than did those using angle brackets. The bearing length of CLT walls on a flexible support reduced the moment lever arms. This increased the tension reaction forces of the metal connectors. Higher density CLT damaged the timber parts at the angle bracket positions that carry the up-lift forces. The flexible supports resulted in plastic deformations and created spaces for local angle brackets bending, whereas the rigid supports resulted in damage to the timber parts of both CLT wall bottom corners caused by their bearing behavior.